2016
DOI: 10.1007/s10103-016-2116-3
|View full text |Cite
|
Sign up to set email alerts
|

Strength training prior to muscle injury potentiates low-level laser therapy (LLLT)-induced muscle regeneration

Abstract: We evaluated whether strength training (ST) performed prior to skeletal muscle cryolesion would act as a preconditioning, improving skeletal muscle regeneration and responsiveness to low-level laser therapy (LLLT). Wistar rats were randomly assigned into non-exercised (NE), NE plus muscle lesion (NE + LE), NE + LE plus LLLT (NE + LE + LLLT), strength training (ST), ST + LE, and ST + LE + LLLT. The animals performed 10 weeks of ST (climbing ladder; 3× week; 80% overload). Forty-eight hours after the last ST ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Similar results were also observed after six days of LLLT applications after cryoinjury [42]. Even after 4 days of cryolesion and LLLT therapy [71] and after 14 days [72] a decrease in muscle levels of TNF-α was found. Pires et al [73] studied tendinitis in rats after 7 and 14 days and they showed that LLLT reduced the TNF-α expression only at chronic phase.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were also observed after six days of LLLT applications after cryoinjury [42]. Even after 4 days of cryolesion and LLLT therapy [71] and after 14 days [72] a decrease in muscle levels of TNF-α was found. Pires et al [73] studied tendinitis in rats after 7 and 14 days and they showed that LLLT reduced the TNF-α expression only at chronic phase.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, it is likely that the expression of growth factors and the increase of bone matrix production favored osteogenesis, consequently improving bone structural and mechanical properties in exercised aged animals. We believe that these findings reflect the intensity of the ST program, i.e., using low repetition/high overload 3 13 14 , in which aged rats displayed a MVCC value, expressed as relative value to the body weight, of 128.81% in comparison to the values obtained previous to ST program practice ( Table 1 ). In addition, it is important to consider that the length of the training period (16 weeks) contributed to the significant differences observed in biomechanical properties.…”
Section: Discussionmentioning
confidence: 50%
“…Photobiomodulation therapy has been shown to relieve or treat many diseases, such as refractory wounds, skin ulcers, and skin flap transplant wounds . This modality uses therapeutic light wavelengths of 600–700 nm, which are perceived as red light by the human retina, to induce photochemical reactions at the irradiation site and thus promote cell proliferation and reduce apoptosis and necrosis to improve prognosis. Accordingly, photobiomodulation therapy may be beneficial to the healing of burn wounds if used to improve the prognosis of the zone of stasis and thus prevent increases in burn depth.…”
mentioning
confidence: 99%